(untitled) (Research, Society and Development, 2020)
The “Projeto Encontro de Saberes1” (PES), written and coordinated by the anthropologist and Professor José Jorge de Carvalho (UNB), is an unprecedented action by the “Instituto Nacional de Ciência e Tecnologia de Inclusão do Ensino Superior e da Pesquisa2” (INCTI/MCT/CNPq), headquartered at UNB. The PES aims decolonize university knowledge through dialogue between indigenous, afro-Brazilian and scientific epistemological matrices in the academic space, represented by the traditional knowledge masters and partner’s doctor professors which together written the menus, the course program and teach classes based on different epistemologies. This article’s aim is to present and discuss the PES methodology, exemplifying it from the experiences that took place at UECE and UFMG, in 2014, reflecting theoretically on this methodology. Because of this, we used a bibliographic search based on Carvalho, Águas, and Floréz and on some post-colonial authors, among them, the Palestinian Edward Said, and in “Ecologia de Saberes3”, by the Portuguese sociologist Boaventura de Souza Santos. Our reflections show that the “Projeto Encontro de Saberes” (PES) may be considered a practical example of post-colonial theory and the Ecology of Knowledge, because in addition to criticizing the hegemony of modern Western scientific thought, it inserts at the University representatives of ancient knowledge, of those who have been “silenced” over the centuries, to dialoguing equally with scientific knowledge, using a methodology that breaks with the mono-epistemic teaching paradigm.